Satellite remote sensing reveals coastal upwelling events in the San Matías Gulf?Northern Patagonia - Pisoni, Juan Pablo (2014)
Coastal upwelling events are effective in fluxing nutrients upward to the euphotic layer, thus promoting the growth of marine phytoplankton. Satellite data may provide useful information to detect and characterize upwelling events in regions of sparse in-situ observations. We analyze the coastal upwelling process on the western San Matías Gulf, on the northern continental shelf of Argentina, based on the analysis of remote sensing and in-situ data. Upwelling events are characterized by their frequency of occurrence and magnitude. During the austral summer we found roughly 6 upwelling-favorable wind events per year. Satellite derived sea surface temperature (SST) data provide evidence of upwelling in 85% of the cases between 2000 and 2008. Analysis of specific events provides clues on the wind forcing characteristics required to generate upwelling, and on characteristic space and time scales of the process. On February 2005 SST data reveal a narrow coastal band (~10 km) of relative cold water extending ~100 km along the west coast of SMG. The SST in this band was 1.5 °C lower than further offshore. Near bottom temperature fluctuations from in-situ daily observations collected at two nearshore locations are significantly correlated with along-shore wind stress, suggesting that coastal upwelling is a dominant process controlling high-frequency temperature fluctuations near-shore. A simple quantitative estimate reveals a volume of upwelled water reaching the sea surface of about 1010 m3 during one relatively intense upwelling event.